2021
DOI: 10.1177/13623613211002052
|View full text |Cite
|
Sign up to set email alerts
|

Training the social brain: Clinical and neural effects of an 8-week real-time functional magnetic resonance imaging neurofeedback Phase IIa Clinical Trial in Autism

Abstract: Autism spectrum disorder is characterized by abnormal function in core social brain regions. Here, we demonstrate the feasibility of real-time functional magnetic resonance imaging volitional neurofeedback. Following up the demonstration of neuromodulation in healthy participants, in this repeated-measure design clinical trial, 15 autism spectrum disorder patients were enrolled in a 5-session training program of real-time functional magnetic resonance imaging neurofeedback targeting facial emotion expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 81 publications
0
19
1
Order By: Relevance
“…ASD participants were recruited from a database used in previous studies ( 47 , 48 ) and in collaboration with local ASD associations. All ASD participants obtained positive results on the gold standard diagnostic instruments, namely parental or caregiver interview [Autism Diagnostic Interview-Revised, ADI-R ( 49 )] and direct structured proband assessment [Autism Diagnostic Observation Schedule, ADOS ( 50 )], and met the current diagnostic criteria for ASD as assessed by the Diagnostic and Statistical Manual of Mental Disorders [5th ed.…”
Section: Methodsmentioning
confidence: 99%
“…ASD participants were recruited from a database used in previous studies ( 47 , 48 ) and in collaboration with local ASD associations. All ASD participants obtained positive results on the gold standard diagnostic instruments, namely parental or caregiver interview [Autism Diagnostic Interview-Revised, ADI-R ( 49 )] and direct structured proband assessment [Autism Diagnostic Observation Schedule, ADOS ( 50 )], and met the current diagnostic criteria for ASD as assessed by the Diagnostic and Statistical Manual of Mental Disorders [5th ed.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, one study on ASD targeted social processing via the connectivity between the left superior temporal sulcus (STS) and the left somatosensory cortex (SC) (54). The other targeted the facial emotion expression processing via the right posterior STS activity (56). Trauma and stressor-related disorders studies focused on the modulation of AMY (41,49,50,52) and the ACC (51) because of their implication in emotion dysregulation, a key symptom in PTSD.…”
Section: 1included Studiesmentioning
confidence: 99%
“…The optimal duration of the follow-up is not yet well established. Some studies reported a sustained improvement after RT-fMRI-NF training for a month(35,36,53,56,59,61,62), while others only after one week(38,43,44,47).Despite the importance of these measures, only 10 studies out of the 30 reviewed collected and reported follow-up data. This leads to a reduction of the clinical relevance of this technique and may lead to an underestimation of the size of the NF effect.…”
mentioning
confidence: 99%
“…These collaborative tasks were also supported by prior research and our domain experts' knowledge. Attending to interpersonal collaboration has been proven to be effective stimuli for autistic children's mirror neuron activation [5,6,14]. The core project team consists of one neuroscientist, two algorithmic engineers (for signal processing and machine learning), two developers (for front-end and back-end development), and three designers (for interaction design and product design).…”
Section: The Starkids System and The Game Designmentioning
confidence: 99%